PERSEPSI MAHASISWA FISIP UNDIP MENGENAI ORGANISASI MAHASISWA EKSTRA KAMPUS SEBAGAI AGEN SOSIALISASI POLITIK - Hisyam Haznil; Dzunuwanus Ghulam Manar; Rina Martini (Journal of Politic and Government Studies, 2014)
External-campus student organization or abbreviated ormek (organisasi mahasiswa ekstra kampus)is an important component in FISIP UNDIP which is politically condensed . As it roles as political socialization agent on the campus, making it a political role model for student.During implementation of political socialization on campus, discovered deficiency. It can be seen from negative perceptions and stigma that attached to the ormek, which is “they comes when they’re needs,and gone when they’re done”. It is very influential on course to political socialization and recognition for students of FISIP UNDIP.The purposes of this study is to determine students' perceptions of role of political socialization agent of external-campus student organizations .In order to determine students' perceptions, researcher used several indicators , such as: knowledge , acceptance statement , disclaimer , opinion , attitude , and assessment . This study used descriptive method with quantitative approach . This research object is perception of FISIP UNDIP’s students regarding external-campus student organizations as political socialization agent.The results shows there are shortcomings of student organizations as an political socialization agent, for instance due to lack of socialization activities , negative stigma and also exclusivity of ormek’s member. The students did not believe its function and role of ormek which is supposed to be political role model and as political socialization agent on campus such as, introducing students about political system on campus, organizing political discussion group or forum, and persuade students to use their right to vote on election. However, a plays as it needs to be reconsidered activities in order to restore ormek’s trust and legitimacy as a good political socialization agent and can be a good political role model for the student.